2015
DOI: 10.1016/j.procs.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Optimization of Solar Micro-grid Using Multi Agent Reinforcement Learning

Abstract: In the distributed optimization of micro-grid, we consider grid connected solar micro-grid system which contains a local consumer, a solar photovoltaic system and a battery. The consumer as an agent continuously interacts with the environment and learns to take optimal actions. Each agent uses a model-free reinforcement learning algorithm, namely Q Learning, to optimize the battery scheduling in dynamic environment of load and available solar power. Multiple agents sense the states of the environment component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 9 publications
(7 reference statements)
1
19
0
Order By: Relevance
“…The comparison result shows that with Boltzmann ε-greedy decision method, the participants in the day-ahead market can receive more profits after sufficient learning iterations, because the value of the temperature variable in the Boltzmann action choosing probability distribution function of every agent (participant) can be adjusted as the iteration proceeds. Similar studies in electricity market simulation and other areas can also be found in [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Literature Review and Main Contributionssupporting
confidence: 74%
See 4 more Smart Citations
“…The comparison result shows that with Boltzmann ε-greedy decision method, the participants in the day-ahead market can receive more profits after sufficient learning iterations, because the value of the temperature variable in the Boltzmann action choosing probability distribution function of every agent (participant) can be adjusted as the iteration proceeds. Similar studies in electricity market simulation and other areas can also be found in [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Literature Review and Main Contributionssupporting
confidence: 74%
“…Taking provisions (1)-(4) into consideration, the methods both in [8][9][10][11][12][13][14][15][16][17][18][20][21][22][23] and in [19,[24][25][26][27][28][29][30][31][32][33] are not quite suitable for modeling and simulating the practical day-ahead electricity market exactly, the reason of which is that in the real day-ahead electricity market, every participant can adjust its bidding strategy within a continuous interval of values, but the literatures suitable for provisions (1)- (3) have assumed that the sets for alternative actions (e.g., bidding strategies) or potential states (e.g., historical MCP) are discrete.…”
Section: Literature Review and Main Contributionsmentioning
confidence: 99%
See 3 more Smart Citations